Understanding the conceptualisation of risk in the context of community dementia care. (July 2018) - Dickins, Marissa; Goeman, Dianne; O'Keefe, Fleur; Iliffe, Steve; Pond, Dimity
Abstract: Risk has become a ubiquitous presence in modern society. For individuals diagnosed with dementia this preoccupation with risk can affect their day-to-day life in many ways. Maintaining autonomy while balancing risks is a continual struggle not only for those living with the disease, but also their carers, family and health professionals. To understand how these different groups of individuals conceptualise the issue of risk for those living with dementia, 83 semi-structured interviews were conducted with people living with dementia, carers, older people without significant experience of dementia, and registered nurses, and staff from a community nursing organisation. These interviews were analysed using Thematic Analysis, which suggested that the risks identified by each group were grounded in their experiences and perspective on dementia. Furthermore, context and understanding of the individual living with dementia and their preferences was central to effectively managing risk in a balanced way, ensuring that 'acceptable risks' were taken to ensure an acceptable quality of life for all involved. These findings highlight that there is no single approach to risk which can be applied to all individuals; rather, a negotiation needs to take place that takes into account the individual's preferences alongside their available resources and means. Highlights: The complex nature of risk in dementia care was echoed by all participant groups. Concepts of acceptable risk were prominent, particularly for people with dementia. Many decisions are made based on the diagnosis of dementia rather than capacity. Removal of risk is often desired; this ignores the possible benefits of some risks.